Romans - Talbert, Charles H. (Smyth & Helwys Bible commentary, 2002)
The conversation begins, Romans 1:1-17 -- The human condition. Part one, Romans 1:18-32 -- The human condition. Part two, Romans 2:1-3:20 -- The divine remedy in relation to the law, Romans 3:21-4:25 -- The ground of future hope, Romans 5:1-11 -- The human condition and its antidote, Romans 5:12-21 -- In Christ the power of sin is broken, Romans 6:1-7:6 -- The role of the law and the divine remedy, Romans 7:7-8:17 -- The future hope, Romans 8:18-39 -- The problem of Israel's unbelief and God's faithfulness, Romans 9-11 -- How slaves of righteousness behave. Part one, Romans 12:1-13:14 -- How slaves of righteousness behave. Part two, Romans 14:1-15:13 -- Making the most of an ending, Romans 15:14-16:27.